2013
DOI: 10.1175/jas-d-12-0112.1
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Predictability of a Three-Dimensional Hurricane in Statistical Equilibrium

Abstract: The internal variability and predictability of idealized three-dimensional hurricanes is investigated using 100-day-long, statistically steady simulations in a compressible, nonhydrostatic, cloud-resolving model. The equilibrium solution is free of the confounding effects of initial conditions and environmental variability in order to isolate the ''intrinsic'' characteristics of the hurricane.The variance of the axisymmetric tangential velocity is dominated by two patterns: one characterized by a radial shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 50 publications
4
21
1
Order By: Relevance
“…While this process may be initiated by asymmetric disturbances, it is unclear whether such variability requires asymmetries. Here we explore variability associated with only the symmetric circulation, which provides a basis for comparison to three-dimensional studies that include asymmetries (Brown and Hakim 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this process may be initiated by asymmetric disturbances, it is unclear whether such variability requires asymmetries. Here we explore variability associated with only the symmetric circulation, which provides a basis for comparison to three-dimensional studies that include asymmetries (Brown and Hakim 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nolan et al (2007) use RCE to examine the sensitivity of tropical cyclogenesis to environmental parameters, and also find the spontaneous development of tropical cyclones. The current paper uses RCE of a specific state, a mature tropical cyclone, to examine the variability and predictability of these storms in an axisymmetric framework; results for three-dimensional simulations are presented in Brown and Hakim (2013).…”
Section: Introductionmentioning
confidence: 99%
“…5d; significant after 12 h), which might be in part due to the difficulty in forecasting rapid intensity changes. Given the absolute error remains the primary verification metrics in various studies (e.g., Elsberry et al 2007;Bhatia and Nolan 2013) and operational centers including the NHC, the mean absolute errors were used in the remainder of this study to make it more comparable to other studies.…”
Section: August 2014mentioning
confidence: 99%
“…Using similar initial perturbations but with the inclusion of environmental vertical wind shear, Zhang and Tao (2013) found that larger magnitudes of shear decrease the intrinsic predictability of the TC, especially during periods of genesis or rapid intensification (RI). Furthermore, Hakim (2013) and Brown and Hakim (2013) explored the possible time scale of intrinsic predictability of several TC characters under an idealized equilibrium framework and found that most features near eyewall region maintained their predictability for no longer than 48 h without considering the ambient environment. It is noteworthy that most studies on TC intensity predictability focused on intrinsic predictability of single or idealized cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation